Fazil Say and Modern and Contemporary Turkish Music (Ex Chordis, 2024)
At the beginning of the XX century, the new Turkish government led by Mustafa Kemal Atatürk took interest in bringing innovation to the Turkish musical scene, jumpstarting a new wave of Turkish music that would fuse traditional elements with the Western compositional style. It is under this light that Fazil Say’s (1970-) music is to be considered: his compositions are windows into his country’s history and traditions, and in each and every one of them he finds new ways to evoke its sounds and sceneries, with and without the presence of actual traditional Turkish instruments. The goal of this work is to explore the history of Turkish music from the beginning of the XX century to the present day, and Fazil Say’s contribution as one of the greatest representatives of his country’s music, through an analysis of the form and structure of two of his compositions for the violin that fully encapsulate his compositional style: the first Sonata for violin and piano and Cleopatra for solo violin.
Keywords: Fazil Say; Violin; Turkish Music; Contemporary Music; Music Analysis